Connexin 43 prevents the progression of diabetic renal tubulointerstitial fibrosis by regulating the SIRT1-HIF-1α signaling pathway. Issue 13 (30th June 2020) - Sun, Xiaohong; Huang, Kaipeng; Haiming, Xiao; Lin, Zeyuan; Yang, Yan; Zhang, Meng; Liu, Peiqing; Huang, Heqing
Abstract: Hyperglycemia-induced renal epithelial-to-mesenchymal transition (EMT) is a key pathological factor in diabetic renal tubulointerstitial fibrosis (RIF). Our previous studies have shown that connexin 43 (Cx43) activation attenuated the development of diabetic renal fibrosis. However, whether Cx43 regulates the EMT of renal tubular epithelial cells (TECs) and the pathological process of RIF under the diabetic conditions remains to be elucidated. In the present study, we identified that Cx43 protein expression was down-regulated in the kidney tissues of db/db mice as well as in high glucose (HG)-induced NRK-52E cells. Overexpression of Cx43 improved renal function in db/db spontaneous diabetic model mice, increased SIRT1 levels, decreased hypoxia-inducible factor (HIF)-1α expression, and reduced production of EMT markers and extracellular matrix (ECM) components. Additionally, Cx43 overexpression inhibited the EMT process and reduced the expression of ECM components such as fibronectin (FN), Collagen I, and Collagen IV in HG-induced NRK-52E cells, whereas Cx43 deficiency had the opposite effects. Mechanistically, Cx43 in a carboxyl-terminal signal transduction-dependent manner could up-regulate SIRT1 expression and enhance SIRT1-dependent deacetylation of HIF-1α to reduce HIF-1α activity, which eventually ameliorated renal EMT and diabetic RIF. Our study indicates the essential role of Cx43 in regulating renal EMT and diabetic RIF via regulating the SIRT1-HIF-1α signaling pathway and provides an experimental basis for Cx43 as a potential target for diabetic nephropathy (DN).